Rules and reasoning : third International Joint Conference, RuleML+RR 2019, Bolzano, Italy, September 16-19, 2019, Proceedings /: third International Joint Conference, RuleML+RR 2019, Bolzano, Italy, September 16-19, 2019, Proceedings. (2019) - Unknown
No abstract available